2011
DOI: 10.1063/1.3599709
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic factors limiting the preservation of aromaticity of adsorbed organic compounds on Si(100): Example of the pyridine

Abstract: Using pyridine as an example, a thermodynamic analysis of the low temperatures adsorption of aromatic organic molecules with a N atom on the Si(100) surface is presented. This study is restricted to the case of an equilibrium with the gas phase. Dative attachment which is the only way to preserve aromaticity is the more stable form of adsorbed pyridine in dilute solutions at low temperatures. Two factors limit the domain of stability of dative attachment: repulsive interactions between dative bonds prevent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 65 publications
(56 reference statements)
8
44
0
Order By: Relevance
“…An example of this universal property is the adsorption of pyridine on Si(100): experimental results [5,6] showed that dative attachment which is the only way to preserve aromaticity is the favored form of adsorbed pyridine in dilute solutions at low temperatures. Recent theoretical analysis [7][8][9][10] confirmed that dative configuration is the more stable configuration. Two factors limit the domain of stability of dative attachment: repulsive interactions between dative bonds prevent them from being present in concentrated solutions while aromaticity contributes to a decrease in the entropy.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…An example of this universal property is the adsorption of pyridine on Si(100): experimental results [5,6] showed that dative attachment which is the only way to preserve aromaticity is the favored form of adsorbed pyridine in dilute solutions at low temperatures. Recent theoretical analysis [7][8][9][10] confirmed that dative configuration is the more stable configuration. Two factors limit the domain of stability of dative attachment: repulsive interactions between dative bonds prevent them from being present in concentrated solutions while aromaticity contributes to a decrease in the entropy.…”
Section: Introductionmentioning
confidence: 82%
“…When heated, aromatic grafted species (dative bonded) are converted to non-aromatic species which explains the vanishing of dative bonds at high temperatures even in dilute solutions as experimentally observed [5,6]. Since aromatic configuration is favored by lower enthalpy, this conversion appears driven by the entropic gain resulting from the vanishing of aromaticity [7,8] justifying here the deliberate use of possible negative contribution of aromaticity to entropy.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations